(untitled) - Vitale, Joe (Hoboken, N.J., 2008)
An online busines guru shares his expertise in a detailed approach to creating and building a profitable Internet business, explaining how to select the right niche, design and construct a Web site, and manage a business.
Keywords: Electronic commerce,Information technology,Internet,Thương mại điện tử,Công nghệ thông tin